Students' Difficulty in Understanding Problems in the Contextual Problem-Solving Process - Samosir, Christina Monika; Herman, Tatang; Prabawanto, Sufyani; Melani, Rini; Mefiana, Syifa Ananda (Universitas Suryakancana, 2024)
The main procedure that students need to master in the problem-solving process is understanding the problem before proceeding to the next steps. This research aims to investigate students' difficulties and the factors causing these difficulties in understanding the problem. This research is qualitative in nature and is based on the philosophy of phenomenology. The research was conducted in an eighth-grade class at one of the Junior High Schools in Bandung, consisting of 28 students. Data collection techniques included tests, interviews, and think-aloud methods. The data collection instruments used were tests and interview guides. The tests used in this research had been previously validated for content, construct, and face validity by mathematics education experts. Data analysis in qualitative research involves data reduction, data presentation, and drawing conclusions. The findings of this research indicate that the difficulties faced by students in understanding the problem include difficulties in comprehending language, difficulties in grasping both explicit and implicit meanings, difficulties in identifying the necessary information, and difficulties in connecting meanings. The main factors causing students' difficulties in understanding the problem are a lack of careful reading skills and a lack of understanding of the concepts held by students.